PEMIKIRAN ABRAHAM GEIGER TENTANG AL-QUR`AN (STUDI ATAS AKULTURASI LINGUISTIK, DOKTRIN DAN KISAH DALAM AL-QUR`AN DARI TRADISI YAHUDI) - Wendi Parwanto (Jurnal Ilmiah Ilmu Ushuluddin, 2019)
Various kinds of orientalist studies on Islam began in the early 19th century, such as studies of the al-Qur`an, hadith, fiqh, and others. One of the orientalist who study Islam from the aspect of the Qur'an is Abraham Geiger. Geiger said, that there are several aspects of the Qur'an that adopted by Jewish traditions. Based on these reasons, the resecher are interested in studying this theme further. This study is a study of library research, with descriptive-analysis method. The conclusion of this study is that some Muslim scholars acknowledge the influence of Islam from other religions, not only from the linguistic aspect of the Qur'an, but also from the empirical-practical, and Islam comes to renew and modify the traditions of previous religions that are not in accordance with values of Islam.